2019
DOI: 10.1002/1878-0261.12542
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone‐like hormone plays a dual role in neuroblastoma depending on PTH1R expression

Abstract: We have previously reported the expression of parathyroid hormone‐like hormone ( PTHLH ) in well‐differentiated, Schwannian stroma‐rich neuroblastic tumors. The aim of this study was to functionally assess the role of PTHLH and its receptor, PTH 1R, in neuroblastoma. Stable knockdown of PTHLH and PTH 1R was conducted in neuroblastoma cell lines to investigate the succeeding phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Recently, the structure and dynamics of the active PTH1R have been shown by cryo-electron microscopy (55). Studies from different research groups have reported that the decreased expression of PTH1R was a poor prognosis factor in multiple types of cancer (56)(57)(58)(59). Although PTH1R was found to be highly expressed in normal kidney samples (Figure 5 and Figure S4), the detailed mechanism of PTH1R in renal function and ccRCC has yet to be fully elucidated and requires further study.…”
Section: Metabolic Shift In Clear Cell Renal Cell Carcinomamentioning
confidence: 99%
“…Recently, the structure and dynamics of the active PTH1R have been shown by cryo-electron microscopy (55). Studies from different research groups have reported that the decreased expression of PTH1R was a poor prognosis factor in multiple types of cancer (56)(57)(58)(59). Although PTH1R was found to be highly expressed in normal kidney samples (Figure 5 and Figure S4), the detailed mechanism of PTH1R in renal function and ccRCC has yet to be fully elucidated and requires further study.…”
Section: Metabolic Shift In Clear Cell Renal Cell Carcinomamentioning
confidence: 99%
“…Neuroblastoma (NB) is an embryonic tumor derived from sympathetic neural crest cells ( 1 , 2 ). It is the most common type of extracranial solid tumor found in children and the most common type of malignant tumor found in infants and young children, with an incidence rate of 10.5 per million children younger than 14 years old ( 3 5 ). The site of the disease is concealed, and NB easily metastasizes ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in neuroblastoma it has been reported that the oncogenic role of PTHrP is a consequence of its intracrine function, as downregulation of its receptor, PTH1R, increased anchorage independent growth and induced a more undifferentiated, invasive phenotype [ 14 ]. Interestingly, in oral cancer, in contrast to what we observed in laryngeal cancer, Chang et al recently reported that PTHrP promotes cell growth via an autocrine/paracrine pathway [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The amino-terminal region of PTHrP (1–34) presents similarities to that of parathyroid hormone, including the PTH/PTHrP type 1 receptor (PTH1R), which is expressed at the plasma membrane of cell lines and tissues [ 11 ]. In vitro and in vivo evidences indicate that PTHrP is involved in tumor initiation, growth and metastatic spread [ 12 14 ]. Finally, the overexpression of PTHrP is associated with poorly differentiated oral squamous cell carcinoma, characterized by poor overall survival [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation